Accrual Accounting and Budgeting Key Issues and Recent Developments - Blöndal, Jón R.. (OECD Publishing, 2003)
Cash and accruals represent two end points on a spectrum of possible accounting and budgeting bases. The cash end of the spectrum has traditionally been applied by OECD member countries for their public sector activities. In recent years there has been a major trend towards the accruals end of the spectrum in member countries. About half of member countries have adopted accruals to one degree or another. The tables at the end of this paper provide details on practices in individual member countries. Several general comments can be made about the use of accruals in member countries...